2016
DOI: 10.2495/cmem-v4-n3-213-220
|View full text |Cite
|
Sign up to set email alerts
|

Influence of homemade ammonium nitrate and fuel oil explosives charge shapes on blast wave propagation

Abstract: The purpose of the paper is to investigate the influence of geometry of charges on the propagation of blast waves. Various shape charges (cylinder, sphere, irregular shape) were used in the field tests. The main type of explosive, homemade ANFO (Ammonium nitrate + fuel oil), was used as the most common used explosives in improvised explosive devices used in terrorist attacks. Characteristics of homemade and industrially made ANFO explosives are different. There were comparing charges of various types of indust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…As far as the reflected wave must be described, the overpressure peak P + (in MPa) represents one of the key parameters to predict, and it depends on several explosion parameters. Based on research efforts of last decades, various closed-form analytical solutions can be found in the literature [54][55][56]. Many other influencing parameters are then involved in the empirical description of an expected blast wave which is confined and can further interact with the ground or with impacted surfaces [52].…”
Section: Explosive or Gas Wavesmentioning
confidence: 99%
See 3 more Smart Citations
“…As far as the reflected wave must be described, the overpressure peak P + (in MPa) represents one of the key parameters to predict, and it depends on several explosion parameters. Based on research efforts of last decades, various closed-form analytical solutions can be found in the literature [54][55][56]. Many other influencing parameters are then involved in the empirical description of an expected blast wave which is confined and can further interact with the ground or with impacted surfaces [52].…”
Section: Explosive or Gas Wavesmentioning
confidence: 99%
“…3). For the numerical investigation reported in this paper, based on the selection of the past experimental outcomes, the attention was thus focused on five different explosives, characterized by mostly different features and thus expected wave propagation properties, as follows [54][55][56]:…”
Section: Explosive or Gas Wavesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, there has been a noticeable shift towards using CAN in agriculture as AN is a detonatable oxidiser that can be used to construct simple yet highly destructive explosives (Brust et al, 2015;Djerdjev et al, 2018). Infamously, used by terrorists AN is inexpensive 6 and small amounts are needed to create explosives (Figuli et al, 2016), which have been used in numerous attacks (Anil Ananthaswamy, 2004;Henry Dodd, 2018). Subsequently, Ireland has banned the sale of AN based fertilisers (The Government Inspector of Explosives, Ireland, 2016), while the European commission prohibits the distribution of fertilisers containing more than 16% AN (ECHA, 2009).…”
Section: Introductionmentioning
confidence: 99%